A method for preparing a sulfur-based metal battery
Patent Information
- Application Number
- CN202311106567.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-16
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-11-16
AI Technical Summary
[0005]本发明针对现有技术中的问题,公开了一种新型的硫基金属电池,改变硫基电池的组成,克服了硫在充放电过程中体积的增大,解决因为硫添加量受限而导致的硫基电池的容量无法改善,减少了硫基电池生产过程中的预处理工艺过程,并且提高了硫基电池的电化学性能
[0053] (1) This invention provides a novel sulfur-based full battery system, which simplifies the sulfur-based battery process, reduces the production time and difficulty of sulfur-based batteries, and facilitates the formation of sulfur-based battery production lines.
Smart Images

Figure BDA0004422331060000141
Abstract
Description
[0001] This application is a divisional application of application number "202211430698.1" entitled "A sulfur-based metal battery and its preparation method". Technical Field
[0002] This invention relates to the field of sulfur-based battery technology, and more specifically to a method for preparing a sulfur-based metal battery. Background Technology
[0003] With the development of lithium battery technology, the energy density of commercially available rechargeable lithium-ion batteries has gradually approached its theoretical limit, making further breakthroughs difficult. Therefore, developing new battery systems is particularly important. Sulfur-based batteries have high theoretical specific energy, and elemental sulfur is extremely abundant on Earth, offering advantages such as affordability and environmental friendliness. Sulfur-based batteries are increasingly being considered the most promising next-generation energy storage system.
[0004] In common sulfur-based batteries, elemental sulfur has poor electronic conductivity, requiring sintering with highly conductive carbon materials before application. The current process for preparing sulfur-carbon composite materials is complex, increasing manufacturing costs. Furthermore, sulfur-based batteries currently face five main problems: First, polysulfide compounds generated during charging and discharging dissolve in the electrolyte, reducing active material, worsening cycle performance, and causing capacity decay. Second, sulfur's poor conductivity hinders high-rate performance. Third, sulfur undergoes significant volume changes during charging and discharging, affecting battery stability. Fourth, traditional sulfur-based batteries require a sulfur-carbon composite slurry to be coated onto the current collector to improve sulfur conductivity. Since the slurry needs sufficient fluidity for uniform coating, the amount of sulfur added is limited by slurry preparation, thus restricting the initial sulfur content in the cathode. Furthermore, the battery capacity is significantly limited. Under these circumstances, during the charging and discharging process, the formation of polysulfide compounds further consumes sulfur in the positive electrode, further reducing the battery's cycle capacity. Therefore, traditional methods for preparing sulfur-based batteries severely restrict capacity improvement due to the limited amount of sulfur added and cycle consumption. Fifth, in the preparation of sulfur-based batteries, such as lithium-sulfur batteries, pre-lithiation treatment is performed to compensate for lithium loss during the first charge-discharge cycle, thereby extending the cycle life of the battery. However, the pre-lithiation process significantly increases the difficulty and time of battery preparation, severely impacting the streamlined preparation process of sulfur-based full batteries. These problems all affect the electrochemical performance of sulfur-based batteries and seriously hinder their commercialization. Summary of the Invention
[0005] This invention addresses the problems in the prior art by disclosing a novel sulfur-based metal battery. By changing the composition of the sulfur-based battery, it overcomes the problem of sulfur increasing in volume during charging and discharging, solves the problem of the inability to improve the capacity of sulfur-based batteries due to the limited amount of sulfur added, reduces the pretreatment process in the production of sulfur-based batteries, and improves the electrochemical performance of sulfur-based batteries.
[0006] This invention is achieved through the following technical solution:
[0007] This invention provides a sulfur-based metal battery. The battery's raw materials include a positive electrode, a negative electrode, a separator, a sulfur source agent, a metal source agent, and a non-aqueous electrolyte. The positive electrode comprises a positive electrode current collector and a positive electrode slurry, the positive electrode slurry containing a positive electrode material, the positive electrode material including sulfur and a host material containing sulfides. The negative electrode comprises a negative electrode current collector and a negative electrode slurry, the negative electrode slurry containing a negative electrode material capable of deintercalation or soluble precipitation of metal. Before or during battery formation, at least a portion of the sulfur source agent and the metal source agent dissolves in the non-aqueous electrolyte to form a saturated non-aqueous electrolyte solution containing the sulfur source agent and the metal source agent. During battery formation, the sulfur source agent and the metal source agent form sulfur and a metal that can be respectively intercalated into the positive and negative electrodes. The metal includes metals capable of forming metal sulfides with sulfur.
[0008] The above-described design of this invention involves a non-aqueous electrolyte containing saturated concentrations of sulfur source agent and metal source agent before or during battery formation. During battery formation, the sulfur source agent and metal source agent form sulfur and metal, which are respectively embedded in the positive and negative electrode materials of the battery, forming a sulfur positive electrode and a metal negative electrode. Adding excess sulfur source agent and metal source agent can promote the continuous embedding of sulfur and metal in the positive and negative electrodes, thereby compensating for the loss of sulfur and metal during charging and discharging. The positive electrode material is selected as a host material for sulfur and sulfides, which can provide embedding sites for sulfur and help overcome the volume increase of sulfur during charging and discharging. The above design also reduces the pretreatment process of traditional sulfur-based batteries, which not only reduces the preparation difficulty and preparation time, but also improves the electrochemical performance of sulfur-based batteries.
[0009] As a further option, the battery formation process involves low-rate formation. During the battery formation process, the sulfur source agent and metal source agent can be decomposed into metal and sulfur.
[0010] As a further improvement, the low concentration is 0.05C ± 0.01C. This facilitates the decomposition and rapid intercalation of the sulfur source and metal source during the formation process.
[0011] As a further option, the sulfur source agent, metal source agent, and non-aqueous electrolyte in the battery raw materials are selected from one of I-IV:
[0012] Ⅰ: The non-aqueous electrolyte contains dissolved sulfur source agent and metal source agent, and exists in the form of a saturated non-aqueous electrolyte solution containing sulfur source agent and metal source agent;
[0013] II: The sulfur source agent and the metal source agent exist in the form of undissolved particles, and the content of the sulfur source agent and the metal source agent is not less than the amount of sulfur source agent and metal source agent required to form a saturated non-aqueous electrolyte solution;
[0014] III: The non-aqueous electrolyte contains dissolved sulfur source agent and metal source agent, and the sulfur source agent and metal source agent also exist in the form of undissolved particles, and the total amount of dissolved sulfur source agent and metal source agent and undissolved particle form is not less than the amount of sulfur source agent and metal source agent required to form a saturated non-aqueous electrolyte solution.
[0015] IV: The non-aqueous electrolyte contains dissolved sulfur source agent and metal source agent, and exists in the form of a saturated non-aqueous electrolyte solution containing sulfur source agent and metal source agent, and the sulfur source agent and metal source agent also exist in the non-aqueous electrolyte solution in the form of undissolved particles.
[0016] As a further option, Option IV is preferred among the above options. When the non-aqueous electrolyte is added to the battery in the form of a saturated non-aqueous electrolyte solution, it can be rapidly decomposed during battery formation, thereby improving formation efficiency.
[0017] As a further embodiment, the host material for the sulfur and sulfides includes one or more of carbon materials, conductive polymers, metal oxides, porous metal materials, and metal sulfides.
[0018] As a further improvement, the host material for the sulfur and sulfides is selected from carbon materials. This is more conducive to the rapid insertion and extraction of sulfur into carbon materials.
[0019] As a further refinement, the carbon material in the cathode material includes one or more of the following: porous carbon, carbon black, graphene, carbon nanotubes, carbon fibers, carbon cloth, graphite, hard carbon, coke, soft carbon, acetylene black, Ketjen black, carbon whiskers, and needle coke. This is used to load sulfur, with the sulfur embedded in the carbon material. This not only facilitates the formation of a sulfur cathode but also allows the carbon material to overcome the volume increase of sulfur.
[0020] As a further embodiment, the negative electrode material is selected from carbon materials, and the metal formed by the metal source agent in the electrolyte can be loaded onto the carbon material by deintercalation; the material from which the metal can be dissolved and precipitated is selected from materials that can form alloys with metals, and the metal and the material that can form alloys with metals form an alloy at the negative electrode, and the metal can be precipitated by dissolution of the alloy.
[0021] As a further improvement, the negative electrode material includes carbon material. Because the insertion / extraction method allows for faster loading of metals into the carbon material, it is more conducive to forming a metal negative electrode in the battery.
[0022] As a further embodiment, the carbon material of the negative electrode material includes one or more of graphite, hard carbon, coke, soft carbon, acetylene black, carbon black, Ketjen black, carbon whiskers, needle coke, carbon fiber, porous carbon, graphene, carbon nanotubes, and carbon cloth; the material capable of forming an alloy with the metal includes one or more of silicon-based materials, tin-based materials, and magnesium-based materials. In this invention, the carbon materials in the positive and negative electrode materials can be selected from the same carbon material.
[0023] As a further embodiment, the sulfur source agent includes a sulfur-containing compound or elemental sulfur that can at least partially dissolve in a non-aqueous electrolyte. This facilitates the formation of sulfur during battery formation, allowing it to be embedded in the cathode material to form a sulfur cathode.
[0024] As a further embodiment, the sulfur source agent includes one or more of Li2S2, Li2S4, Li2S6, Li2S8, Na2S2, Na2S4, Na2S6, Na2S8, lithium sulfide, sodium sulfide, potassium sulfide, calcium sulfide, tin sulfide, aluminum sulfide, magnesium sulfide, and iron sulfide.
[0025] As a further embodiment, the metal source agent is a compound containing the target metal that can at least partially dissolve in a non-aqueous electrolyte.
[0026] As a further refinement, the metal source agent includes one or more of the following: Li₂S₂, Li₂S₄, Li₂S₆, Li₂S₈, Na₂S₂, Na₂S₄, Na₂S₆, Na₂S₈, lithium sulfide, lithium iodide, sodium iodide, sodium sulfide, magnesium sulfide, aluminum sulfide, and calcium sulfide. The selection of the metal source agent can be based on the specific requirements of the sulfur-based battery type; for example, in sodium-sulfur batteries, a metal source agent capable of forming a sodium anode is selected. Since the lithium metal anode in lithium-sulfur batteries exhibits better insertion / extraction efficiency and greater capacity, the metal source agent is generally further preferred from lithium metal source agents.
[0027] As a further improvement, both the sulfur source agent and the metal source agent can be selected from the same source, including one or more of Li₂S₂, Li₂S₄, Li₂S₆, Li₂S₈, Na₂S₂, Na₂S₄, Na₂S₆, Na₂S₈, lithium sulfide, and sodium sulfide. After decomposition, these substances can be directly intercalated into the positive and negative electrodes, respectively, which helps reduce the introduction of trace impurities such as other metals or non-sulfur substances into the electrolyte.
[0028] As a further option, the non-aqueous electrolyte contains a solvent.
[0029] As a further option, the solvent includes an organic liquid electrolyte.
[0030] As a further embodiment, the organic liquid electrolyte includes one of ethers and esters.
[0031] As a further embodiment, the ether-based organic liquid electrolyte includes dimethyl ether.
[0032] As a further embodiment, the specific surface area of the host material of the sulfur and sulfides is greater than 20 m². 2 / g. Because the sulfur formed in the electrolyte has a relatively large particle size, the suitable specific surface area of sulfur and the host material for sulfides are conducive to promoting sulfur migration and stable intercalation, and overcoming the volume change of sulfur during battery charge-discharge cycles. Therefore, the specific surface area is greater than 20m². 2 The host material of sulfur and sulfides with a concentration of / g is preferred.
[0033] As a further embodiment, the specific surface area of the host material of the sulfur and sulfides is greater than 100 m². 2 / g. A larger specific surface area allows the cathode material to load more sulfur, which helps improve the battery's initial specific capacity and cycle performance.
[0034] As a further embodiment, the positive electrode slurry also includes a catalyst, wherein the amount of catalyst added to the positive electrode slurry is 0.1wt%-50wt%.
[0035] As a further embodiment, the catalyst comprises one of a metal and a metal compound, and the particle size of the catalyst is less than 2 μm.
[0036] As a further embodiment, the metal includes one of Fe, Cu, and Co.
[0037] As a further improvement, the catalyst has a particle size of less than 500 nm. The smaller the particle size of the catalyst, the greater its surface energy, the larger its specific surface area, and the better its catalytic effect.
[0038] As a further embodiment, the catalyst is added to the cathode slurry at an amount of 0.1 wt%-10 wt%; as an even further embodiment, the catalyst is added to the cathode slurry at an amount of 5 wt%-10 wt%. The cathode material can be loaded with the catalyst, which is more conducive to the catalyst's catalytic activity. The presence of the catalyst in the cathode avoids the poor dispersibility or side reactions caused by adding other types of catalysts in the electrolyte as solutes. During battery formation, the catalyst helps to lower the energy barrier between sulfur and the cathode material, thereby promoting sulfur intercalation into the cathode material. Simultaneously, during battery charging and discharging, it promotes the reaction between sulfur and metals.
[0039] As a further embodiment, the positive electrode slurry of the battery also includes a binder, a positive electrode conductive agent, and a positive electrode dispersant, and the negative electrode slurry of the battery also includes a binder, a negative electrode conductive agent, and a negative electrode dispersant.
[0040] As a further embodiment, the mass ratio of the positive electrode material, binder, and positive electrode conductive agent is 8:1:1.
[0041] As a further embodiment, the mass ratio of the negative electrode material, binder, and negative electrode conductive agent is 94:3:3.
[0042] This invention also provides a method for preparing a sulfur-based metal battery, comprising:
[0043] S1: Add the positive electrode material, binder and positive electrode conductive agent to the dispersant according to the mass ratio, add the catalyst, mix evenly and then coat it on the positive electrode current collector, and heat it to obtain the positive electrode;
[0044] S2: Add the negative electrode material, binder and negative electrode conductive agent to the dispersant according to the mass ratio, mix evenly and then coat it on the negative electrode current collector, and heat it to obtain the negative electrode;
[0045] S3: Preparation of non-aqueous electrolyte, followed by assembly of sulfur-based metal batteries, using one of the methods selected from I-IV:
[0046] Ⅰ: Add excess sulfur source agent and metal source agent to the organic liquid electrolyte, ensuring that the added mass of sulfur source agent and metal source agent is not less than the mass of the sulfur source agent and metal source agent that can form a saturated non-aqueous electrolyte solution in the non-aqueous electrolyte; heat and stir to dissolve and form a non-aqueous electrolyte solution with saturated concentration of sulfur source agent and metal source agent, and filter; take the positive electrode, separator, and negative electrode to assemble a soft-pack battery, add the obtained organic liquid electrolyte solution into the inside of the soft-pack battery, and seal it;
[0047] II: Assemble a soft-pack battery by taking the positive electrode, separator, and negative electrode. Add an excessive amount of sulfur source agent and metal source agent solid particles to the inside of the soft pack. The added mass of sulfur source agent solid particles and metal source agent solid particles shall not be less than the mass of the sulfur source agent and metal source agent forming a saturated non-aqueous electrolyte solution in the non-aqueous electrolyte. Add the organic liquid electrolyte to the inside of the soft-pack battery and seal it.
[0048] III: Add sulfur source agent and metal source agent to the organic liquid electrolyte, heat and stir to dissolve and form a non-aqueous electrolyte containing sulfur source agent and metal source agent; assemble a soft-pack battery with positive electrode, separator and negative electrode; add sulfur source agent solid particles and metal source agent solid particles inside the soft pack; add the obtained non-aqueous electrolyte inside the soft-pack battery and seal it; the total added mass of dissolved sulfur source agent and metal source agent and undissolved sulfur source agent solid particles and metal source agent solid particles in the non-aqueous electrolyte shall not be less than the mass of sulfur source agent and metal source agent that can form a saturated non-aqueous electrolyte solution in the non-aqueous electrolyte;
[0049] IV: Add excess sulfur source agent and metal source agent to the organic liquid electrolyte. The added mass of sulfur source agent and metal source agent shall not be less than the mass of sulfur source agent and metal source agent that can form a saturated non-aqueous electrolyte solution in the non-aqueous electrolyte. Heat and stir to dissolve and form a non-aqueous electrolyte solution with saturated concentration of sulfur source agent and metal source agent, and filter. Take the positive electrode, separator, and negative electrode to assemble a soft-pack battery. Add not less than 0g of sulfur source agent solid particles and metal source agent solid particles to the inside of the soft-pack battery. Add the obtained non-aqueous electrolyte solution to the inside of the soft-pack battery and seal it.
[0050] S4: The assembled battery is formed, and the formed battery is then subjected to charge and discharge tests.
[0051] As a further embodiment, in S1, the binder is PVDF (polyvinylidene fluoride), the positive electrode conductive agent is carbon black, the positive electrode dispersant is NMP (N-methylpyrrolidone), and the positive electrode current collector is aluminum foil; the coating thickness is 90μm-110μm; the heating temperature is 70℃-90℃, and the heating time is 7h-9h. In S2, the binder is PVDF, the negative electrode conductive agent is carbon black, the negative electrode dispersant is NMP, and the negative electrode current collector is copper foil; the coating thickness is 90μm-110μm; the heating temperature is 70℃-90℃, and the heating time is 7h-9h. In S3, the heating and stirring temperature is 50℃-70℃, and the heating and stirring time is 70h-80h.
[0052] The features and beneficial effects of this invention are as follows:
[0053] (1) This invention provides a novel sulfur-based full battery system, which simplifies the sulfur-based battery process, reduces the production time and difficulty of sulfur-based batteries, and facilitates the formation of sulfur-based battery production lines.
[0054] (2) This invention is not limited to lithium-sulfur batteries; it is also applicable to sodium-sulfur batteries, magnesium-sulfur batteries, aluminum-sulfur batteries, and calcium-sulfur batteries.
[0055] (3) By using the decomposition of sulfur source agent and metal source agent, the sulfur and metal in the non-aqueous electrolyte are continuously embedded in the positive and negative electrodes, thereby making up for the consumption of sulfur and metal during the charging and discharging process of the battery and improving the capacity of sulfur-based batteries.
[0056] (4) It solves the problem of limited sulfur addition in sulfur-based batteries, thereby improving the capacity and cycle performance of sulfur-based batteries.
[0057] (5) The host material for sulfur and sulfides is porous carbon, and the sulfur produced is embedded in the porous carbon, which overcomes the volume change of sulfur during the charging and discharging process.
[0058] (6) In the sulfur-based metal battery of the present invention, before the battery is formed, the positive electrode is not limited to being loaded with sulfur, and the negative electrode is not limited to containing metal. The present invention is particularly suitable for sulfur-free positive electrode and metal-free negative electrode, which not only reduces the process of preparing sulfur positive electrode and metal negative electrode, but also improves the electrochemical performance of sulfur-based battery. Detailed Implementation
[0059] To facilitate understanding of the sulfur-based metal battery of the present invention, a more comprehensive description of the preparation method of the sulfur-based metal battery of the present invention will be given below, and embodiments of the present invention will be provided, but this does not limit the scope of the present invention.
[0060] Example 1
[0061] (1) Preparation of positive electrode sheet
[0062] With a specific surface area of 50m 2 / g of porous carbon, PVDF, and carbon black (Super P) are added to NMP in a mass ratio of 8:1:1. After being mixed evenly, the mixture is coated onto aluminum foil with a coating thickness of 100μm. After heating at 80℃ for 8 hours, the coating is punched using a punching machine and then ready for use.
[0063] (2) Preparation of negative electrode sheet
[0064] Hard carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 94:3:3. After being mixed evenly, the mixture was coated onto copper foil with a thickness of 100 μm. After heating at 80°C for 8 hours, the coating was punched using a die-casting machine and then ready for use.
[0065] (3) Preparation of saturated electrolyte
[0066] 2.3 g of lithium sulfide and 4.8 g of sulfur were added to 10 mL of DME solution, heated and stirred at 60 °C for 72 h, cooled, and filtered with filter paper to obtain a saturated Li2S4 electrolyte.
[0067] (4) Battery manufacturing
[0068] Assemble a pouch cell using the positive electrode, separator, and negative electrode. Add 0.1g of lithium sulfide particles inside the pouch cell; add 2g of saturated Li₂S₄ electrolyte and seal. Form the battery at a 0.05C rate. Perform charge-discharge tests on the formed battery.
[0069] Example 2
[0070] (1) Preparation of positive electrode sheet
[0071] With a specific surface area of 100m 2 / g of porous carbon, PVDF, and carbon black (Super P) are added to NMP in a mass ratio of 8:1:1. After being mixed evenly, the mixture is coated onto aluminum foil with a coating thickness of 100μm. After heating at 80℃ for 8 hours, the coating is punched using a punching machine and then ready for use.
[0072] (2) Preparation of negative electrode sheet
[0073] Hard carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 94:3:3. After being mixed evenly, the mixture was coated onto copper foil with a thickness of 100 μm. After heating at 80°C for 8 hours, the coating was punched using a die-casting machine and then ready for use.
[0074] (3) Preparation of saturated electrolyte
[0075] 2.3 g of lithium sulfide and 4.8 g of sulfur were added to 10 mL of DME solution, heated and stirred at 60 °C for 72 h, cooled, and filtered with filter paper to obtain a saturated Li2S4 electrolyte.
[0076] (4) Battery manufacturing
[0077] Assemble a pouch cell using the positive electrode, separator, and negative electrode. Add 0.1g of lithium sulfide particles inside the pouch cell; add 2g of saturated Li₂S₄ electrolyte and seal. Form the battery at a 0.05C rate. Perform charge-discharge tests on the formed battery.
[0078] Example 3
[0079] (1) Preparation of positive electrode sheet
[0080] With a specific surface area of 200 m² 2 / g of porous carbon, PVDF, and carbon black (Super P) are added to NMP in a mass ratio of 8:1:1. After being mixed evenly, the mixture is coated onto aluminum foil with a coating thickness of 100μm. After heating at 80℃ for 8 hours, the coating is punched using a punching machine and then ready for use.
[0081] (2) Preparation of negative electrode sheet
[0082] Hard carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 94:3:3. After being mixed evenly, the mixture was coated onto copper foil with a thickness of 100 μm. After heating at 80°C for 8 hours, the coating was punched using a die-casting machine and then ready for use.
[0083] (3) Preparation of saturated electrolyte
[0084] 2.3 g of lithium sulfide and 4.8 g of sulfur were added to 10 mL of DME solution, heated and stirred at 60 °C for 72 h, cooled, and filtered with filter paper to obtain a saturated Li2S4 electrolyte.
[0085] (4) Battery manufacturing
[0086] Assemble a pouch cell using the positive electrode, separator, and negative electrode. Add 0.1g of lithium sulfide particles inside the pouch cell; add 2g of saturated Li₂S₄ electrolyte and seal. Form the battery at a 0.05C rate. Perform charge-discharge tests on the formed battery.
[0087] Example 4
[0088] (1) Preparation of positive electrode sheet
[0089] With a specific surface area of 200 m² 2 / g of porous carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 8:1:1. Then, 0.5wt% of copper catalyst powder (particle size of 2μm) was added. After mixing evenly, the mixture was coated on aluminum foil with a coating thickness of 100μm. After heating at 80℃ for 8 hours, the coating was punched using a punching machine and then ready for use.
[0090] (2) Preparation of negative electrode sheet
[0091] Hard carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 94:3:3. After being mixed evenly, the mixture was coated onto copper foil with a thickness of 100 μm. After heating at 80°C for 8 hours, the coating was punched using a die-casting machine and then ready for use.
[0092] (3) Preparation of saturated electrolyte
[0093] 2.3 g of lithium sulfide and 4.8 g of sulfur were added to 10 mL of DME solution, heated and stirred at 60 °C for 72 h, cooled, and filtered with filter paper to obtain a saturated Li2S4 electrolyte.
[0094] (4) Battery manufacturing
[0095] Assemble a pouch cell using the positive electrode, separator, and negative electrode. Add 0.1g of lithium sulfide particles inside the pouch cell; add 2g of saturated Li₂S₄ electrolyte and seal. Form the battery at a 0.05C rate. Perform charge-discharge tests on the formed battery.
[0096] Example 5
[0097] (1) Preparation of positive electrode sheet
[0098] With a specific surface area of 200 m² 2 / g of porous carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 8:1:1. Then, 0.5wt% of copper catalyst powder (particle size of 500nm) was added. After mixing evenly, the mixture was coated on aluminum foil with a coating thickness of 100μm. After heating at 80℃ for 8h, the coating was punched using a punching machine and then ready for use.
[0099] (2) Preparation of negative electrode sheet
[0100] Hard carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 94:3:3. After being mixed evenly, the mixture was coated onto copper foil with a thickness of 100 μm. After heating at 80°C for 8 hours, the coating was punched using a die-casting machine and then ready for use.
[0101] (3) Preparation of saturated electrolyte
[0102] 2.3 g of lithium sulfide and 4.8 g of sulfur were added to 10 mL of DME solution, heated and stirred at 60 °C for 72 h, cooled, and filtered with filter paper to obtain a saturated Li2S4 electrolyte.
[0103] (4) Battery manufacturing
[0104] Assemble a pouch cell using the positive electrode, separator, and negative electrode. Add 0.1g of lithium sulfide particles inside the pouch cell; add 2g of saturated Li₂S₄ electrolyte and seal. Form the battery at a 0.05C rate. Perform charge-discharge tests on the formed battery.
[0105] Example 6
[0106] (1) Preparation of positive electrode sheet
[0107] With a specific surface area of 200 m² 2 / g of porous carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 8:1:1. Then, 0.5wt% of copper catalyst powder (particle size of 100nm) was added. After mixing evenly, the mixture was coated on aluminum foil with a coating thickness of 100μm. After heating at 80℃ for 8h, the coating was punched using a punching machine and then ready for use.
[0108] (2) Preparation of negative electrode sheet
[0109] Hard carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 94:3:3. After being mixed evenly, the mixture was coated onto copper foil with a thickness of 100 μm. After heating at 80°C for 8 hours, the coating was punched using a die-casting machine and then ready for use.
[0110] (3) Preparation of saturated electrolyte
[0111] 2.3 g of lithium sulfide and 4.8 g of sulfur were added to 10 mL of DME solution, heated and stirred at 60 °C for 72 h, cooled, and filtered with filter paper to obtain a saturated Li2S4 electrolyte.
[0112] (4) Battery manufacturing
[0113] Assemble a pouch cell using the positive electrode, separator, and negative electrode. Add 0.1g of lithium sulfide particles inside the pouch cell; add 2g of saturated Li₂S₄ electrolyte and seal. Form the battery at a 0.05C rate. Perform charge-discharge tests on the formed battery.
[0114] Example 7
[0115] (1) Preparation of positive electrode sheet
[0116] With a specific surface area of 200 m² 2 / g of porous carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 8:1:1. Then, 5wt% of copper catalyst powder (particle size of 100nm) was added. After mixing evenly, the mixture was coated on aluminum foil with a coating thickness of 100μm. After heating at 80℃ for 8h, the coating was punched using a punching machine and then ready for use.
[0117] (2) Preparation of negative electrode sheet
[0118] Hard carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 94:3:3. After being mixed evenly, the mixture was coated onto copper foil with a thickness of 100 μm. After heating at 80°C for 8 hours, the coating was punched using a die-casting machine and then ready for use.
[0119] (3) Preparation of saturated electrolyte
[0120] 2.3 g of lithium sulfide and 4.8 g of sulfur were added to 10 mL of DME solution, heated and stirred at 60 °C for 72 h, cooled, and filtered with filter paper to obtain a saturated Li2S4 electrolyte.
[0121] (4) Battery manufacturing
[0122] Assemble a pouch cell using the positive electrode, separator, and negative electrode. Add 0.1g of lithium sulfide particles inside the pouch cell; add 2g of saturated Li₂S₄ electrolyte and seal. Form the battery at a 0.05C rate. Perform charge-discharge tests on the formed battery.
[0123] Example 8
[0124] (1) Preparation of positive electrode sheet
[0125] With a specific surface area of 200 m² 2 / g of porous carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 8:1:1. Then, 10wt% of copper catalyst powder (particle size of 100nm) was added. After mixing evenly, the mixture was coated on aluminum foil with a coating thickness of 100μm. After heating at 80℃ for 8h, the coating was punched using a punching machine and then ready for use.
[0126] (2) Preparation of negative electrode sheet
[0127] Hard carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 94:3:3. After being mixed evenly, the mixture was coated onto copper foil with a thickness of 100 μm. After heating at 80°C for 8 hours, the coating was punched using a die-casting machine and then ready for use.
[0128] (3) Preparation of saturated electrolyte
[0129] 2.3 g of lithium sulfide and 4.8 g of sulfur were added to 10 mL of DME solution, heated and stirred at 60 °C for 72 h, cooled, and filtered with filter paper to obtain a saturated Li2S4 electrolyte.
[0130] (4) Battery manufacturing
[0131] Assemble a pouch cell using the positive electrode, separator, and negative electrode. Add 0.1g of lithium sulfide particles inside the pouch cell; add 2g of saturated Li₂S₄ electrolyte and seal. Form the battery at a 0.05C rate. Perform charge-discharge tests on the formed battery.
[0132] Example 9
[0133] (1) Preparation of positive electrode sheet
[0134] With a specific surface area of 200 m² 2 / g of porous carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 8:1:1. Then, 10wt% of copper catalyst powder (particle size of 100nm) was added. After mixing evenly, the mixture was coated on aluminum foil with a coating thickness of 100μm. After heating at 80℃ for 8h, the coating was punched using a punching machine and then ready for use.
[0135] (2) Preparation of negative electrode sheet
[0136] Hard carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 94:3:3. After being mixed evenly, the mixture was coated onto copper foil with a thickness of 100 μm. After heating at 80°C for 8 hours, the coating was punched using a die-casting machine and then ready for use.
[0137] (3) Preparation of saturated electrolyte
[0138] 3.9 g of sodium sulfide and 4.8 g of sulfur were added to 10 mL of DME solution, heated and stirred at 60 °C for 72 h, cooled, and filtered with filter paper to obtain a saturated Na2S4 electrolyte.
[0139] (4) Battery manufacturing
[0140] Assemble a pouch cell using the positive electrode, separator, and negative electrode. Add 0.1g of sodium sulfide granules inside the pouch cell. Add 2g of saturated Na2S4 electrolyte and seal the cell. Form the battery at a 0.05C rate. Perform charge-discharge tests on the formed battery.
[0141] Comparative Example 1
[0142] (1) Preparation of positive electrode sheet
[0143] With a specific surface area of 200 m² 2 / g of porous carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 8:1:1. Then, 10wt% of copper catalyst powder (particle size of 100nm) was added. After mixing evenly, the mixture was coated on aluminum foil with a coating thickness of 100μm. After heating at 80℃ for 8h, the coating was punched using a punching machine and then ready for use.
[0144] (2) Preparation of negative electrode sheet
[0145] Hard carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 94:3:3. After being mixed evenly, the mixture was coated onto copper foil with a thickness of 100 μm. After heating at 80°C for 8 hours, the coating was punched using a die-casting machine and then ready for use.
[0146] (3) Preparation of saturated electrolyte
[0147] 2.3 g of lithium sulfide and 4.8 g of sulfur were added to 10 mL of DME solution, heated and stirred at 60 °C for 72 h, cooled, and filtered with filter paper to obtain a saturated Li2S4 electrolyte.
[0148] (4) Battery manufacturing
[0149] Assemble a pouch cell using the positive electrode, separator, and negative electrode. Add 0.1g of lithium sulfide particles inside the pouch cell. Add 2g of saturated Li₂S₄ electrolyte and seal the cell. Perform charge-discharge tests.
[0150] Comparative Example 2
[0151] (1) Preparation of sulfur-carbon positive electrode sheet
[0152] Sulfur-carbon cathode (sulfur-carbon mass ratio of 3:1), PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 8:1:1 and coated onto aluminum foil with a coating thickness of 100 μm. After heating at 80°C for 8 hours, the coating was punched using a die-casting machine and then ready for use.
[0153] (2) Preparation of negative electrode sheet
[0154] Hard carbon, PVDF, and carbon black (Super P) were added to NMP in a mass ratio of 94:3:3. After being mixed evenly, the mixture was coated onto copper foil with a thickness of 100 μm. After heating at 80°C for 8 hours, the coating was punched using a die-casting machine and then ready for use.
[0155] (3) Preparation of pre-lithiated negative electrode sheet
[0156] Place the negative electrode sheet, add 4g of electrolyte (1M LiTFSI-DOL / DME (5:5vol)), then place a lithium strip slightly larger than the electrode sheet with a thickness of 120μm. After placing it under high pressure for 48h, remove the lithium sheet to obtain the pre-lithiated negative electrode sheet.
[0157] (4) Preparation of saturated electrolyte
[0158] 2.3 g of lithium sulfide and 4.8 g of sulfur were added to 10 mL of DME solution, heated and stirred at 60 °C for 72 h, cooled, and filtered with filter paper to obtain a saturated Li2S4 electrolyte.
[0159] (5) Battery manufacturing
[0160] Assemble a pouch cell using the positive electrode, separator, and pre-lithiated negative electrode. Add 0.1g of lithium sulfide particles inside the pouch cell. Add 2g of saturated Li₂S₄ electrolyte and seal the cell. Perform charge-discharge tests.
[0161] Validation Result Analysis
[0162] Table 1. Parameters and Battery Performance of Examples and Comparative Examples
[0163]
[0164] We conducted experiments to compare the effects of the specific surface area of the host material (sulfur and sulfides) with different specific surface areas, the content of the catalyst, and the particle size of the catalyst on the capacity of the prepared sulfur-based batteries, thereby obtaining the optimal preparation method for sulfur-based batteries, as shown in Examples 1-9.
[0165] We first investigated the effect of host materials with different specific surface areas of sulfur and sulfides on the capacity of sulfur-based batteries, as shown in Examples 1-3. We found that as the specific surface area of the carbon material increased, the initial specific capacity and capacity retention of the battery improved. We believe that a larger specific surface area allows for the loading of more sulfur onto the carbon, which is beneficial for improving the initial specific capacity and cycle performance of the battery. We further selected host materials with a specific surface area greater than 100 m². 2 / g.
[0166] We further investigated the effect of catalysts on the electrochemical performance of sulfur-based batteries. Adding catalysts to the batteries improves their cycle performance, as shown in the comparison between Examples 4-8 and Examples 1-3. The sulfur-based batteries with added catalysts exhibited better first-cycle specific capacity and capacity retention than those without. We believe that adding catalysts inside the positive electrode firstly enhances the catalytic activity of the catalyst. We consider that porous carbon materials facilitate catalyst dispersion and further enhance catalytic activity. Secondly, it lowers the energy barrier between sulfur and carbon, allowing the generated sulfur to quickly embed within the porous carbon during battery formation, thus forming a sulfur positive electrode. During battery re-discharge, the catalyst promotes charge transfer between sulfur and metal, thereby increasing the rate of electrochemical activity during charge and discharge, and improving the battery's specific capacity and capacity retention. Based on this, we further investigated the effect of catalyst particle size on the catalytic effect, as shown in Examples 4-6. When the catalyst particle size is smaller, both the initial specific capacity and capacity retention of the battery increase. We believe this is because smaller catalyst particles have higher surface energy and a larger specific surface area, resulting in better catalytic performance. Therefore, we further selected a catalyst particle size of less than 500 nm. Furthermore, the amount of catalyst added also affects the capacity of the sulfur-based battery. As shown in Examples 6-8, with the increase of catalyst addition, the initial specific capacity and capacity retention of the sulfur-based battery increase. We believe that increasing the amount of catalyst added increases the number of active sites. However, excessive catalyst addition may affect the amount of other substances added to the cathode, and the cost of the catalyst is also high, so the amount added must be considered in terms of cost. In summary, we further selected a catalyst addition amount of 0.1 wt%-10 wt%. The catalytic effect is optimal when the catalyst addition amount is between 5 wt% and 10 wt%, so we further selected a catalyst addition amount of 5 wt%-10 wt%.
[0167] Li in non-aqueous electrolyte + Lithium is formed during battery formation and embedded in the negative electrode material. If the particle size of the embedded particles increases, the embedding difficulty increases and the number of embedded particles decreases, resulting in a reduction in battery capacity. As shown in Example 9, sodium sulfide and sulfur are added to the non-aqueous electrolyte. Sodium ions have a larger diameter than lithium ions, making it more difficult for ions to transport and de-embed in the negative electrode material. This results in a significant decrease in the first-cycle specific capacity of the battery in Example 9. The first-cycle specific capacity of the battery in Example 8 is approximately three times that of Example 9.
[0168] The prepared sulfur-based battery was formed at a rate of 0.05C, which facilitated the decomposition of sulfur and metal source agents in the non-aqueous electrolyte, forming sulfur and metal embedded in the positive and negative electrode materials of the battery, respectively, thus forming a metal negative electrode and a sulfur positive electrode. This preparation method can overcome the volume change of sulfur during charge and discharge, thereby improving the conductivity of sulfur. Furthermore, it allows for the addition of excess sulfur and metal source agents, enabling the continuous embedding of sulfur and metal in the positive and negative electrodes, overcoming the problem of reduced battery capacity due to the loss of sulfur and metal. As shown in Example 8 and Comparative Example 1, the first-cycle specific capacity of the battery in Example 8 was 15 times that of the battery in Comparative Example 1. It is evident that formation facilitates the formation of a metal negative electrode and a sulfur positive electrode in the sulfur-based battery, which is beneficial for improving battery capacity, and the first-cycle specific capacity of the battery is significantly increased.
[0169] Based on this, we compared the sulfur-based battery prepared using the present invention with a sulfur-based battery prepared by a conventional method, as shown in Example 8 and Comparative Example 2. The sulfur-based battery prepared by the present invention exhibits better first-cycle specific capacity and capacity retention than that prepared by a conventional method. Furthermore, the method of the present invention can reduce the negative electrode manufacturing process, such as the pre-lithiation process in lithium-sulfur batteries, thereby significantly reducing the manufacturing difficulty and time, and facilitating the design of a streamlined production line for sulfur-based batteries.
[0170] In summary, the novel sulfur-based full battery system of this invention not only simplifies the production process of sulfur-based batteries but also improves their electrochemical performance.
[0171] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a sulfur-based metal battery, characterized in that, The raw materials of the sulfur-based metal battery include a sulfur source agent, a metal source agent, and a non-aqueous electrolyte; before or during the formation of the sulfur-based metal battery, at least a portion of the sulfur source agent and the metal source agent are dissolved in the non-aqueous electrolyte to generate a saturated non-aqueous electrolyte solution containing the sulfur source agent and the metal source agent. Before the formation of the sulfur-based metal battery, the positive electrode does not contain sulfur and the negative electrode material does not contain metal; during the formation of the sulfur-based metal battery, at least a portion of the sulfur source agent and the metal source agent form sulfur and metal in the self-saturated non-aqueous electrolyte solution and are respectively embedded in the positive electrode and the negative electrode. Before the formation of the sulfur-based metal battery, the specific surface area of the positive electrode is greater than 20 m². 2 / g; The battery is configured for a low rate of 0.05C ± 0.01C. The negative electrode material is a carbon material; The sulfur source agent and the metal source agent are both selected from the same type, including one or more of lithium sulfide and sodium sulfide.
2. The preparation method according to claim 1, characterized in that, Before or during the formation of a sulfur-based metal battery, a specific preparation method for dissolving at least a portion of the sulfur source agent and the metal source agent in a non-aqueous electrolyte to generate a saturated non-aqueous electrolyte solution containing the sulfur source agent and the metal source agent is selected from one of I-IV: Ⅰ: Add excess sulfur source agent and metal source agent to the non-aqueous electrolyte, ensuring that the added mass of sulfur source agent and metal source agent is not less than the mass of the sulfur source agent and metal source agent that can form a saturated non-aqueous electrolyte solution in the non-aqueous electrolyte; heat and stir to dissolve and form a saturated non-aqueous electrolyte solution with saturated concentration of sulfur source agent and metal source agent, filter, and inject the solution; II: Inject the non-aqueous electrolyte, and then add an excess of sulfur source agent and metal source agent solid particles into the non-aqueous electrolyte. The added mass of sulfur source agent solid particles and metal source agent solid particles shall not be less than the mass of the sulfur source agent and metal source agent forming a saturated non-aqueous electrolyte solution in the non-aqueous electrolyte. III: Add sulfur source agent and metal source agent to the non-aqueous electrolyte, heat and stir to dissolve and form an unsaturated non-aqueous electrolyte containing sulfur source agent and metal source agent, and inject the solution; then add sulfur source agent solid particles and metal source agent solid particles to the unsaturated non-aqueous electrolyte; the total added mass of dissolved sulfur source agent and metal source agent and undissolved sulfur source agent solid particles and metal source agent solid particles in the unsaturated non-aqueous electrolyte shall not be less than the mass of sulfur source agent and metal source agent that can form a saturated non-aqueous electrolyte solution in the non-aqueous electrolyte; IV: Add excess sulfur source agent and metal source agent to the non-aqueous electrolyte, ensuring that the added mass of sulfur source agent and metal source agent is not less than the mass of sulfur source agent and metal source agent that can form a saturated non-aqueous electrolyte solution in the non-aqueous electrolyte; heat and stir to dissolve and form a non-aqueous electrolyte solution with saturated concentration of sulfur source agent and metal source agent, filter, and inject the solution; then add not less than 0g of sulfur source agent solid particles and metal source agent solid particles to the saturated non-aqueous electrolyte solution.
3. The preparation method according to claim 2, characterized in that, The heating and stirring temperature in sections I, III, and IV is 50℃-70℃, and the heating and stirring time is 70h-80h.
4. The preparation method according to claim 1, characterized in that, The sulfur source agent is a sulfur-containing compound or elemental sulfur that can be at least partially dissolved in a non-aqueous electrolyte; the metal source agent is a compound containing a target metal that can be at least partially dissolved in a non-aqueous electrolyte.
5. The preparation method according to claim 1, characterized in that, The sodium sulfide includes one or more of Na2S2, Na2S4, Na2S6, and Na2S8; the lithium sulfide includes one or more of Li2S2, Li2S4, Li2S6, and Li2S8.
6. The preparation method according to claim 1, characterized in that, The non-aqueous electrolyte includes an organic liquid electrolyte, which includes one of ethers and esters; the ether-based organic liquid electrolyte includes dimethyl ether.
7. The preparation method according to claim 1, characterized in that, The preparation method includes the steps of dissolving at least a portion of the sulfur source agent and the metal source agent in a non-aqueous electrolyte to generate a saturated non-aqueous electrolyte solution containing the sulfur source agent and the metal source agent before or during the formation of the sulfur-based metal battery, as well as the step of forming the sulfur-based metal battery.
8. The preparation method according to claim 7, characterized in that... The metal includes lithium or sodium.
Citation Information
Patent Citations
Capacitor battery and preparation method thereof
CN109841425A
Non-aqueous electrolyte secondary battery
JP2005158313A
Method for manufacturing lithium sulfur battery
KR1020050041717A